Two Greek Funerary Inscriptions From Zoara/Ghor As-Safi In Jordan (Early Byzantine Zoora)* - Kokkinos, Nikos; Politis, Konstantinos D. (Jordan Journal for History and Archaeology, 2022)
Inscriptions from the Byzantine period in southern Jordan include a corpus of mainly funerary Greek and Aramaic texts discovered in recent years in the Ghor as-Safi area of southern Jordan. Containing more than 456 epitaphs from the An-Naq‘ cemetery of Zoara (Early Byzantine Zoora), this extraordinary collection dating from the fourth to the seventh century AD continues to expand. Many more texts are being currently studied and forthcoming in separate publications. As part of that effort, two additional Greek inscriptions recognized as having originated from Zoara are presented here. The first – significant in filling gaps in the early Byzantine social mosaic – commemorates Faustina, a name appearing for the first time, joining eight other Latin female names, and dating last to 16 February AD 503. This date falling within Year 397 of the Era of the Province of Arabia is known only from one inscription in the corpus, but the Indiction of Year 11 mentioned is unique. Equally unique is the name of Theodotos as an ecclesiastical authority, a deacon, a presbyter, or even the city-bishop. The decoration of a large sun disk with a cross in the middle could represent the Constantinian sun god Sol Invictus converted to Christianity. The second inscription is also rare in commemorating one Bargonnas, a name probably deriving from the epithet given to Simon/Peter in Matthew’s Gospel (16:17): Βαριωνᾶς.